The Incidence of Saints' Names in relation to Scottish Fairs (Proceedings of the Society of Antiquaries of Scotland, 1918)
Some time before 1888, a Royal Commission was appointed to inquire into the subject of market rights and tolls within the United Kingdom, and the Commissioners during the ensuing years published a series of volumes dealing with the minutes of evidence taken before them, statistics regarding the various markets and fairs, and their reports thereon. Altogether nearly 900 places are mentioned in which fairs are or were held, and of the latter some 311 are specified to have been held on the anniversary day of some particular saint. A synopsis of saints' names with the places in which fairs named after them were held is presented.